Cyclic partition for the groups of PSL(2,41) and PSL(2,43) - Niran Sabah; Noor Alhuda Samir Salem (Al-Qadisiyah Journal of Pure Science, 2021)
The ordinary character table and the character table (cha.ta.) of rational representations (ra.repr.) for projective special linear groups                   (2,41) and  (2,43) find in this work to find the cyclic partition for each group